An External Addition of Soy Protein Isolate Hydrolysate to Sourdough as a New Strategy to Improve the Quality of Chinese Steamed Bread. Issue 1 (20th October 2015) - Liu, Xiao; Li, Teng; Liu, Boyan; Zhao, Hongfei; Zhou, Fang; Zhang, Bolin
Abstract: Soy protein isolate (SPI) was hydrolyzed and then its hydrolysate (Hyd‐SPI) was supplemented to dough. The dough fermented by a starter consisting of L actobacillus paralimentarius 412 and A nqi 's yeast was applied to manufacture Chinese steamed bread. Addition of 1% Hyd‐SPI to dough is found to significantly improve the farinograph and extensograph values. Moreover, 1% Hyd‐SPI stimulates the growth and metabolism of the starter culture better compared with the control and thus improves the sourdough fermentation. The sourdough supplemented with 1% Hyd‐SPI observed by scanning electron microscopy contains starch granules that are largely hydrolyzed. Additionally, the sourdough has more free amino acids than the control. A total of 45 volatile compounds are recognized in the Chinese steamed breads containing 1% Hyd‐SPI. This is the first report that SPI hydrolysate is used to improve the quality of Chinese steamed bread products. Practical Applications: Chinese steamed bread, as a traditional grain product that is made with sourdough, has been widely consumed in Northern China and many Southeastern Asian countries for its taste and rich nutrition. The better the performance of the sourdough, the better the quality of the Chinese steamed bread. This study uses a hydrolyzed soy protein isolate (Hyd‐SPI) as an external supplement to enhance the fermentation performance and rheological properties of sourdough. Currently, this technique has been extended to local producers for the manufacture of the sourdough‐based steamed bread.